(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2014)
Managing grain moisture content is important because maximum economic return can be achieved by marketing at a certain moisture level of grain. Post-harvest management dictates that grains must be dried to certain levels to avoid development of fungal and insect problems, respiration and germination. However, over drying can also a lead to economic losses. Most farmers are aware of fungal development in moist grains but few are aware that they make less profit by over drying. Moreover, there are also bean varieties which genetically retain more water than others and hence can be safer and have more economic returns compared to others. But, this also should be matched to the rain pattern in a growing region. We compared six varieties of beans (KAT B1, KAT B9, and Kakunzu (KKZ), Rose Coco (GLP2/RCC), Kenya Tamu and KAT X56) grown in the South Eastern region of Kenya and found significant differences in dry moisture content, physical properties and grain weights. The Rose Coco and KAT X56 varieties had the highest moisture content retention but the KKZ variety the lowest. This explained why KKZ is favoured more by famers in arid areas with less rain during fruit maturation.